Engines of Truth - Schneider, Wendie Ellen (Yale University Press, 2021)
During the Victorian era, new laws allowed more witnesses to testify in court cases. At the same time, an emerging cultural emphasis on truth-telling drove the development of new ways of inhibiting perjury. Strikingly original and drawing on a broad array of archival research, Wendie Schneider’s examination of the Victorian courtroom charts this period of experimentation and how its innovations shaped contemporary trial procedure. Blending legal, social, and colonial history, she shines new light on cross-examination, the most enduring product of this time and the “greatest legal engine ever invented for the discovery of truth.” This title was made Open Access by libraries from around the world through Knowledge Unlatched.